DIURNAL RAPTORS ON BANDEALIT RESORT AT MERU BETIRI NATIONAL PARK, EAST JAVA, INDONESIA - Arif Mohammad Siddiq; Hari Sulistiyowati; Rendy Setiawan; Muhammad Kurniawan; Puji Firmansyah (Treubia, 2023)
Meru Betiri National Park (MBNP) is one of the conservation areas as a habitat for diurnal raptors in East Java. However, the updated information on diurnal raptors in MBNP is still limited, with the latest information recorded in 2014. Therefore, this study aims to inventory the species composition of diurnal raptors in Bandealit Resort at MBNP. This research was conducted in April-June 2022 using the point count method with an observation radius of 1 km. We sampled a total of three observation points in three forest cover types i.e dense vegetation (primary forest), semi-dense vegetation (secondary forest-plantation), and low vegetation (coastal forest). Data collection included diurnal raptors species, frequency of encounters for each species, time of encounter, coordinate points, and activity (flyover, soaring, and perched). The results showed the presence of 10 diurnal raptors at the Bandealit Resort MBNP which consisted of two families (Accipitridae and Falconidae). Based on the IUCN Red list of threatened species, there are eight species of least concern (LC), one species of near threatened (NT), and one species of endangered (EN). The frequency of encounters shows that Crested Serpent-eagle (Spilornis cheela) has the highest frequency value (20%), while the Spotted Kestrel (Falco moluccensis) and Changeable Hawk-Eagle (Nisaetus cirrhatus) have the lowest frequency value (4%). Furthermore, as a special record, the Javan Hawk-eagle (N. bartelsi) is found with a fairly high frequency of encounters (11%). Approximately 75.71% of observed diurnal raptors are in soaring activity. Moreover, based on their distribution area, the primary forest has the highest composition of diurnal raptor species encountered.